2014
DOI: 10.11114/jets.v2i4.449
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Head Start Staff Participation in Classroom-Based Professional Development

Abstract: Factors associated with Head Start staff participation in a classroom-based professional development project to promote their use of evidence-based child learning opportunity practices and evidence-based responsive teaching procedures were examined in a study of 36 teachers and teacher assistants in 19 different classrooms. The factors constituting the focus of investigation included work climate, staff belief appraisals (career aspirations, personal motivation, Developmentally Appropriate Practices beliefs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The findings, taken together, provided support for the hypothesis that more frequent provision of or engagement in evidence-based capacity-building professional development engenders early childhood intervention practitioners' use of family-centered participatory practices (Dunst, 2017b;Espe-Sherwindt, 2008). The results also indicate that early childhood intervention practices that are judged as important and acceptable are more likely to influence the relationship between capacity-building professional development and practitioner use of family-centered practices in a manner consistent with previous findings (Strain et al, 2012;Strohmeier, Mule, & Luiselli, 2014;Trivette, Raab, & Dunst, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…The findings, taken together, provided support for the hypothesis that more frequent provision of or engagement in evidence-based capacity-building professional development engenders early childhood intervention practitioners' use of family-centered participatory practices (Dunst, 2017b;Espe-Sherwindt, 2008). The results also indicate that early childhood intervention practices that are judged as important and acceptable are more likely to influence the relationship between capacity-building professional development and practitioner use of family-centered practices in a manner consistent with previous findings (Strain et al, 2012;Strohmeier, Mule, & Luiselli, 2014;Trivette, Raab, & Dunst, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…This type of relationship was found in a study of PD provided to a group of Head Start teachers. The social validity ratings given to an intervention practice taught during the PD influenced the teachers’ responsiveness to learning the intervention practices (Trivette, Raab, & Dunst, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Head Start teachers, practitioner social validity ratings of practices constituting the focus of professional development were found to be related to how engaged the practitioners were in the professional development (Trivette, Raab, & Dunst, 2014). In another study of parents' judgments of the social validity of interest-based child language learning practices, results showed that social validity was not only directly related to the parents' fidelity of use of the practices with their children but indirectly related to the rates of changes in child language development mediated by the frequency of child engagement in interest-based language learning activities (Dunst, Raab, & Hamby, 2016).…”
Section: Social Validity Researchmentioning
confidence: 99%